2021
DOI: 10.1017/dmp.2021.48
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Lockdown on Body Weight, Eating Habits, and Physical Activity of Jordanian Children and Adolescents

Abstract: Objective: The lockdown for the COVID-19 pandemic affects lifestyle patterns globally and impacts children and adolescents. This study aims to assess the effect of the lockdown on body weight, eating habits, and physical activity of Jordanian youth (children and adolescents). Methods: A cross-sectional study was conducted on a sample of 477 Jordanian children and adolescents aged 6-17 y. The study tool was a structured validated questionnaire. It comprised 4 parts, including a general de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
105
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(127 citation statements)
references
References 37 publications
15
105
0
7
Order By: Relevance
“…Furthermore, Androutsos et al claimed that 66.9% of parents observed that the physical activity of their children was declined [11]. Characteristically, Ng et al stated that 20% of the Irish teenagers took part in their study, had increased their physical activity,30% had no changes during the pandemic and 50% of them characterized by physical inactivity [17].Those observations were also confirmed in Al Hourani's et al study, which found that more than 50% of adolescents did not exercise or exercise for less than an hour [12]. It should be noted that Orgilés et al emphasized the role of the family relationships, highlighting good family relationships, as an enhancing factor to adolescents exercise [8].…”
Section: Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…Furthermore, Androutsos et al claimed that 66.9% of parents observed that the physical activity of their children was declined [11]. Characteristically, Ng et al stated that 20% of the Irish teenagers took part in their study, had increased their physical activity,30% had no changes during the pandemic and 50% of them characterized by physical inactivity [17].Those observations were also confirmed in Al Hourani's et al study, which found that more than 50% of adolescents did not exercise or exercise for less than an hour [12]. It should be noted that Orgilés et al emphasized the role of the family relationships, highlighting good family relationships, as an enhancing factor to adolescents exercise [8].…”
Section: Resultsmentioning
confidence: 80%
“…In another study, Al Hourani et al showed that 70% of adolescents spent more than 3 hours per day in front of a screen [7]. Francisco et al also observed that before quarantine, MARCH-AUGUST 2021 |VOLUME 1, ISSUE 3 they used to spend less than 1 hour [7], [12] and during the pandemic the use was increased. In addition, in Italy, Portugal and Spain the The reports from the articles proved that COVID-19 pandemic affected adolescents including their sleep habits.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations